Effect of Feeding Time and Nutrient Degradability in Sorghum Stover Based Feeding System on Ruminal Microbial Protein Synthesis in Crossbred Cattle (Journal of Basic and Applied Research in Biomedicine, 2022)
Farmers fed sorghum stover as staple roughages for low milk yielding dairy cattle was surveyed followed by in vitro and in vivo experiments to enhance rumen microbial protein synthesis in cattle without altering the quantity of forage / feed ingredients. The survey revealed that majority of farmers fed roughages twice daily during morning and evening and supplemented with groundnut cake at forenoon and evening along with de-oiled rice bran in drinking water. The in vitro degradability characteristics of the sorghum stover and supplemental feeds viz., groundnut cake, sesame cake, coconut cake and de-oiled rice bran were studied by Rumen Simulation Technique (RUSITEC). The half time (t1/2) of organic matter and nitrogen for sorghum stover were 27 ± 4 and 34 ± 4 hour, respectively. The respective t1/2 time of organic matter and nitrogen for the commonly fed supplemental feeds viz., coconut cake and de-oiled rice bran were 7 ± 1 and 15 ± 2 and 8 ± 0 and 7 ± 1 hour, respectively. Altering the feeding strategy based on t1/2 value of organic matter and nitrogen sources did not increased the rumen microbial protein yield by in vitro / in vivo experiments. There was comparable microbial nitrogen synthesis per kg metabolic body weight of animal between evolved and farmer’s feeding strategies in sorghum stover based feeding system (0.480 vs. 0.485 g / d). Hence, it was concluded that altering the feeding time based on nutrient degradability in sorghum stover based feeding system did not increased the rumen microbial protein synthesis.